From 3D to 2D Transition Metal Nitroprussides by Selective Rupture of Axial Bonds. Issue 48 (8th August 2019) - Ávila, Yosuan; Osiry, Hernández; Plasencia, Yosdel; Torres, Ana E.; González, Marlene; Lemus‐Santana, Ana A.; Reguera, Edilso
Abstract: 1‐methyl‐2‐pyrrolidone (1m2p) is a solvent with proven abilities for 2D‐solid exfoliation due to its extremely high surface tension. In principle, such a feature could be used also to induce the selective breaking of certain bonds in solids to obtain new materials. Such a hypothesis is demonstrated in this study for transition metal nitroprussides, where 2D solids are obtained from 3D frameworks by selective rupture of axial bonds. This contribution discusses the mechanism involved in such molecular manufacture. The crystal structure for the formed 2D solids was solved and refined from XRD powder patterns recorded using synchrotron radiation. Mössbauer, IR and Raman spectra provided fine details on the electronic structure of the resulting new series of layered materials. The experimental information was complemented with calculations for the molecule configuration in its non‐activated and activated forms. In the obtained 2D solids, neighboring layers of about 1 nm of thickness remain separated by activated 1m2p molecules. The interaction between neighboring layers is of a physical nature, without the presence of a chemical bond between them, as corresponds to a 2D material. Abstract : Split decision : 1‐methyl‐2‐pyrrolidone appears as a relevant solvent for molecular manufacture. It is able to induce a selective rupture of certain bond in solid, making possible the preparation of new and modified materials. Such potentiality is demonstrated in the contribution for the selective rupture of axial CN−T bonds in 3D transition metal nitroprussides to form the 2D analogues.